Molecular and Immunological Study for Detection of BK Human Polyoma Virus in Patient with Hemorrhagic Cystitis in some Iraq People (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2020)
Hemorrhagic cystitis (HC) is considering one of the important complications in lower urinary tract hematuria, hemorrhage and dysuria are most common symptom .In hemorrhagic cystitis, short-term hematuria can also be seen in bladder infections as a result of viral infection. Viral cystitis represents another form of non-bacterial urinary tract infection affected adult and children. Human polyomavirus BK type I and V, Adenovirus types 21 and 11 and CMV viruses also can be cause of hemorrhagic cystitis. The aim of the present study work was to find out the relation of polyoma virus BKVS with acute syndrome consists of hematuria and studying the sequence and molecular genotyping of such virus with certain immunological factors among infected patients. This study was performed on two hundred and thirty bloody urine and blood specimens were collected from patients that  were selected to eliminate other causes of hematuria, the patients group comprised 170 male and 60 female age group 6 -65 years.  Patient samples (Urine and serum) were collected for detection of Human polyoma virus (BKVS) by using conventional PCR technique and immunological parameters. All bloody urine cultured on ordinary media to differentiate between viral and bacterial infection. The result of  current  study was found that 154 samples (67%) have positive bacterial culture which excluded and the other 76 samples(33%) give negative bacterial culture were included as suspected  a viral cause of hematuria. All negative culture cases was classified  as  4(5.26%) patients with glomerulonephritis ,15 (19.73%) chronic renal failure,14(18.42%)urinary tract infection ,27(35.5%) kidney transplantation ,16(21.5%) cystitis. The age range distribution mostly in age group more than 50 years at 21 (27.6 %) as higher percent in comparison with other age groups as well as the male percentage higher than female. All urine patients 76 with 25 urines samples of control were analyzed by Convention PCR for detection BVS. It was found only 9(11.8%) as a positive result. There were different immunological parameters used to evaluate function immune system such as IFN-α, IFN-ɤ, TNF-α, CD4 and CD8, to maintain the disease status. The result of IFN-α IFN-ɤ, CD4, CD8 showed a higher significant level in comparison with control samples at P value (< 0.05), while the ‘result of TNF-α showed no significant difference in comparison with control. It is  noted that the result of CD4 and CD8 in relation to age group showed that the age > 50 years have higher level of infection  than other. The percentage of BKVS is more dominant in adult age in both sexes, mostly at age more than 50 years. Bioinformatics was used for specific primers designed from the data base sequence information, for capsid protein genes (vp1, and agno) genes in (NCBI) and Sequencing of DNA And Sequencing analysis were used to diagnosis genes of BKVS .Conclusion: This study showed that the detection of Human polyoma virus in bloody urine could be applicable in hospitals laboratories by rapid decony cell.  It  reported the application of qPCR assay for rapid specific and highly sensitive for confirmative detection of BKVS as causative agents in hemorrhagic cystitis. The elevation level of immunological  factors(CD4,CD8,TNF-α,IFN-α and IFN-ɤ) act as monitor the  immune response  to effectiveness of BK virus on Hemorrhagic cystitis  patients  by ELISA assay. Sequencing and phylogenetic analysis reported that  Baghdad and Al-Najaf population are infected with hemorrhagic cystitis induced by BKVS is more predominantly with newly genotype.